The taxonomic status of Myotis levis levis and Myotis levis dinellii (Mammalia: Chiroptera: Vespertilionidae) - Miranda,João M. D. (2013)
Investigating the Myotis levis complex is important for understanding the taxonomic status of the two subspecies currently recognized in it: Myotis levis levis (I. Geoffroy, 1824) and M. levis dinellii Thomas, 1902. Both M. levis levis and M. levis dinellii have been recently observed in sympatry in Argentina. This finding suggests that these populations might in fact correspond to distinct species rather than subspecies, as they have traditionally been designated. By using a multivariate morphometric approach, we demonstrate that M. l. levis has secondary sexual dimorphism in several measurements, with females being larger than males; sexual dimorphism was not detected in M. levis dinellii. However, we found morphometric differences between the two taxa. These differences exceeded those documented for other Neotropical Myotis. Based on their sympatry, morphological, and morphometrical differences, we propose a change in the status of both subspecies to M. levis and M. dinellii.